COLOR METAPHORIN ENGLISH AND INDONESIAN SONG LYRICS - Khaerul Umam; Deli Nirmala (Universitas Negeri Makassar, 2020)
This study contrasts the concept of color metaphor in English and Indonesian song lyrics. In the concept of color metaphor, meaning must be interpreted based on certain similarities between primary and secondary meanings. This isdescriptive qualitative research. The method used in this research is simak method. Padan method is used to analyze the data.The results show that the concept of color metaphor in English and Indonesian song lyrics have some similarities and differences. The striking similarities are found in the black color metaphor concept which symbolizes darkness, white color symbolizes purity, yellow colorsymbolizesenlightenment, and gray colorsymbolizes sadness. However, the different concepts of color metaphor are found in blue, red, and green colors.